What a Dog! - Hunt,Roderick (Oxford University press, 1986)
"What a Dog!" by Roderick Hunt is a charming story from the Oxford Reading Tree series. In this tale, the characters encounter a lively dog that brings excitement and a bit of chaos to their day. As they interact with the dog, they experience fun moments and some humorous mishaps. The story highlights themes of friendship, the joy of pets, and the adventures that come with them. With engaging illustrations and a playful narrative, it's an enjoyable read for young children, encouraging them to appreciate the companionship of animals.
Keywords: Textbook